Organizacje przedsiębiorcze w sieci - Morawski, Mieczysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The new type of enterprise leaning on knowledge economy is being shaped. It is connected with creating new values for a customer. And enterprising behaviour and attitudes are best visible in enterprising organizations. They create the net of connections to meet the growing demands of customers and to cope with the growing competitiveness. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 192-199